Obwodowe komisje wyborcze jako najniższy szczebel w strukturze polskich organów wyborczych - Szarek, Katarzyna (Polityka i Społeczeństwo, 2021)
Currently, election administration is often discussed in the mass media and is of great interest to the public. This is probably due to the recent local elections carried out on 16 November 2014, during which there was a problem among others with the election information technology system and delays in the announcement of the results of the vote. The objective is to assess certain issues of the regional electoral commissions, their mode of appointment, composition, organisation of work, position in the composition and tasks of these committees, which are involved in conducting all forms of elections. The article analyzes the solutions adopted in the Polish electoral law for regional electoral commissions, as well as containing conclusions and recommendations. This is important in view of the ongoing legislative work on the amendment to the Electoral Code of 2011.